Effects of mechanical activation and sodium hexametaphosphate on formation of magnesium orthosilicate ceramic powder - Kong, Koon Yi (2024)
Magnesium Orthosilicate, a mineral belonging to the olivine group, is composed of magnesium, silicon, and oxygen atoms. Its crystalline structure provided unique characteristics such as a high melting point, biocompatibility, and chemical stability. These properties made Magnesium Orthosilicate suitable for use as substitute parts of hard tissue. Consequently, the quest for efficient synthesis methods for forsterite became increasingly significant due to its potential applications in industries such as construction, electronics, and energy storage. Despite the potential applications of forsterite in industries such as construction and biomedicine, there remained a knowledge gap regarding the development of efficient synthesis methods that could reliably produce highquality forsterite with precise control over its properties, such as particle size, morphology, and purity. Thus, this experiment explored various synthesis techniques, including high shear mixing and planetary ball milling, to determine optimal conditions for producing Magnesium Orthosilicate. Additionally, the experiment investigated the effects of the addition of Sodium Hexametaphosphate (SHMP) on viscosity to aid in the mass production of Magnesium Orthosilicate, aiming to enhance the scalability of the production. The most effective mechanical activation was found to be using high shear mixing with a mixing duration of 1 hour. Based on these findings, the optimum calcination conditions were determined to be at 1100°C with a holding time of 2 hours. The addition of SHMP allowed better dispersion and was capable of producing pure nanoparticle Magnesium Orthosilicate. As the weight percent (wt%) of SHMP addition increased, the particle size decreased, but this compromised the purity of the Magnesium Orthosilicate. The optimum waterto-solid ratio was found to be 6.871. These findings provided a more efficient way to synthesize Magnesium Orthosilicate, especially for mass production.